2016
DOI: 10.3233/thc-161199
|View full text |Cite
|
Sign up to set email alerts
|

A single task assessment system of upper-limb motor function after stroke

Abstract: Abstract. BACKGROUND: Nowadays, stroke is a leading cause of disability in adults. Assessment of motor performance has played an important role in rehabilitation for post stroke patients. Therefore, it is quite important to develop an automatic assessment system of motor function. OBJECTIVE: The purpose of this study is to assess the performance of the single task upper-limb movements quantitatively among stroke survivors. METHODS: Eleven normal subjects and thirty-five subjects with stroke were involved in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 19 publications
0
11
2
Order By: Relevance
“…Several objective kinematic features have been shown to have a strong correlation with clinical scales [43], [44], [13], [40], [30]. The relation between the measures shown in the present study and the level of impairment, although it follows the theoretical aspects that qualify motor function in stroke patients, does not have a high statistical power due to the low sample size and the small range of impairment severity in the population.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…Several objective kinematic features have been shown to have a strong correlation with clinical scales [43], [44], [13], [40], [30]. The relation between the measures shown in the present study and the level of impairment, although it follows the theoretical aspects that qualify motor function in stroke patients, does not have a high statistical power due to the low sample size and the small range of impairment severity in the population.…”
Section: Discussioncontrasting
confidence: 65%
“…The majority of studies use kinematic measures in activities of daily living or while performing functional tasks, such as reach-to-grasp tasks [39], [20], [13], [40]. Some studies used inertial measurement units while performing simple movements that include flexion/extension, abduction and supination of limb segments [30], [40]. In this work, a new distributed sensing system was developed and tested in an upper limb model, healthy and stroke subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the functional and motor performance of other rehabilitation patient populations have been studied extensively (e.g. stroke [3][4][5]), the dynamic progress and motor learning of upper limb amputees has been relatively neglected. Meanwhile, an emergence of quantitative movement-based measures, enabled by motion capture technology, have gained popularity and have allowed for reliable study of movement and motor control.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that the partial anisotropy of the cortical spinal tract in the affected side after stroke has decreased, which is closely related to subsequent exercise recovery [14], [15]. It is proposed that the decrease in the anisotropy of the affected part after stroke is related to poor exercise scores [16], [17]. In addition, some studies have suggested that the degree of anisotropy reduction in the affected part of the early stroke can predict the degree of prognosis of the affected limb [18]- [20].…”
Section: Introductionmentioning
confidence: 99%